Corporate Governance in India (Global Journal of Management and Business Research, 2011)
Corporate Governance is concerned with the establishment of a system whereby the directors are entrusted with responsibilities and duties in relation to the direction of corporate affairs. It is concerned with accountability of concerned persons, who are managing it towards the stakeholders. It is concerned with the morals, ethics, values, conduct and behaviors of the company and its management. This paper deals with the governance of business organization in the context of business corporate sector.
Keywords: Concerned; Management; Governance; Corporate